2003
DOI: 10.1200/jco.2003.05.190
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Tumor Markers With Prognostic Impact in Dukes’ Stages B and C Colorectal Cancer Patients

Abstract: The present study indicates that 17p, 18q, and 20q genotypes, and TP53 mutation status add information in the subclassification of Dukes' B and C patients and may have impact on the choice of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
66
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 73 publications
8
66
1
3
Order By: Relevance
“…There have been several attempts to identify this subset of patients both at histopathological and more often at molecular levels. At the genomic level, few studies have focused on early-stage colorectal cancer [3][4][5][6] and of those studies that focused on early-stage colorectal cancer, the analysis was limited to few chromosomes. 7,8 Therefore, there is currently a need to profile primary tumours from early-stage colorectal cancer using genome-wide scanning techniques that can also be integrated into current laboratory practices.…”
mentioning
confidence: 99%
“…There have been several attempts to identify this subset of patients both at histopathological and more often at molecular levels. At the genomic level, few studies have focused on early-stage colorectal cancer [3][4][5][6] and of those studies that focused on early-stage colorectal cancer, the analysis was limited to few chromosomes. 7,8 Therefore, there is currently a need to profile primary tumours from early-stage colorectal cancer using genome-wide scanning techniques that can also be integrated into current laboratory practices.…”
mentioning
confidence: 99%
“…However, the prognostic role of TP53-inactivating mutations is still in question (Iacopetta et al, 2006). Similarly, the impacts of epidermal growth factor receptor (EGFR) over-expression, loss of heterozygosity in chromosome 18q, somatic adenomatous polyposis coli (APC), and KRAS mutations on survival remain unclear (Diep et al, 2003;Spano et al, 2005;Walther et al, 2009).…”
Section: Molecular Markersmentioning
confidence: 99%
“…In these cases, inactivating mutations (29% of all CRCs) are correlated with advanced stage and vascular and lymphatic involvement. Diep et al (2003) showed that TP53 mutations affecting the L3 zinc-binding domain and lower survival rate in the subclassification of Dukes' B and C patients and may have an impact on the ideal treatment strategy. However, the prognostic role of TP53-inactivating mutations is still in question (Iacopetta et al, 2006).…”
Section: Molecular Markersmentioning
confidence: 99%
“…Allelic imbalances (AIs) appearing as loss of heterozygosity (LOH) or as microsatellite instability (MSI) have been detected in the circulating DNA of patients with a variety of malignancies, such as non-small-cell lung cancer (Sozzi et al, 1999), renal cell carcinoma (Gonzalgo et al, 2002), bladder cancer (Utting et al, 2002), breast cancer (Silva et al, 1999), colon cancer (Diep et al, 2003), and malignant melanoma (Taback et al, 2004). Nawroz et al (1996) first demonstrated that AIs could be detected in the plasma/ serum DNA of head and neck SCC, suggesting that circulating tumour-associated DNA in the blood of patients with oral SCC can be a key determinant in predicting tumour recurrences or metastasis.…”
mentioning
confidence: 99%